Entrepreneurial Persistence beyond Survival: Measurement and Determinants - Marco Caliendo; Maximilian Goethner; Martin Weißenberger (Institute of Labor Economics (IZA), 2019)
Entrepreneurial persistence is demonstrated by an entrepreneur's continued positive maintenance of entrepreneurial motivation and constantly-renewed active engagement in a new business venture despite counter forces or enticing alternatives. It is thus a crucial factor for entrepreneurs when pursuing and exploiting their business opportunities and to realize potential economic gains and benefits. Using rich data on a representative sample of German business founders, we investigate the determinants of entrepreneurial persistence. Next to observed survival we also construct a hybrid persistence measure capturing also the motivational dimension of persistence. We analyze the influence of individual-level (human capital and personality) and business-related characteristics on both measures as well as their relative importance. We find that the two indicators emphasize different aspects of persistence. For the survival indicator, the predictive power is concentrated in business characteristics and human capital, while for hybrid persistence, the dominant factors are business characteristics and personality. Finally, we show that results are heterogeneous across subgroups. In particular, formerly-unemployed founders do not differ in survival chances, but they are more likely to lack a high psychological commitment to their business ventures.
Keywords: L26; M13; 330; entrepreneurship; start-ups; persistence; survival